TARBIYAH DALAM PERSPEKTIF AL-QUR’AN: ANALISIS SEMANTIK TERHADAP KATA RABB DAN RELEVANSINYA DENGAN KONSEP PENDIDIKAN ISLAM - Wela Maryani; Ali Musolli Sohibi Harahap; Samsuddin; Balkis Nur Azizah (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to analyze the semantic meaning of the term Rabb in the Qur’an and explain its implications for the concept of Islamic education, particularly within the framework of tarbiyah. The research employs a library-based method with a Qur’anic semantic approach through lexical analysis, contextual examination of verses, and semantic relation mapping. Data were obtained from primary sources consisting of Qur’anic verses containing the word Rabb, as well as secondary sources such as classical and contemporary tafsir works, tarbiyah literature, and studies in Arabic linguistics. The findings indicate that the term Rabb encompasses a broad range of meanings, including creation, nurturing, regulation, guidance, and the gradual perfection of human nature (fitrah). These results affirm that tarbiyah in the Qur’anic perspective is not merely the transmission of knowledge, but an integral and continuous process that involves spiritual, moral, intellectual, and social development. The study concludes that understanding the comprehensive meaning of Rabb provides a theological and philosophical foundation for a holistic Islamic educational concept that is gradual, character-oriented, and centered on the development of human fitrah toward maturity and piety. Keywords: education, islamic education, rabb, tarbiah, tarbiah islamiah